A Novel Member of the Trehalose Transporter Family Functions as an H+-Dependent Trehalose Transporter in the Reabsorption of Trehalose in Malpighian Tubules - Kikuta, Shingo; Hagiwara-Komoda, Yuka; Noda, Hiroaki; Kikawada, Takahiro (Frontiers in Physiology, 2012)
In insects, Malpighian tubules are functionally analogous to mammalian kidneys in that they not only are essential to excrete waste molecules into the lumen but also are responsible for the reabsorption of indispensable molecules, such as sugars, from the lumen to the principal cells. Among sugars, the disaccharide trehalose is highly important to insects because it is the main hemolymph sugar to serve as a source of energy and carbon. The trehalose transporter TRET1 participates in the transfer of newly synthesized trehalose from the fat body across the cellular membrane into the hemolymph. Although transport proteins must play a pivotal role in the reabsorption of trehalose in Malpighian tubules, the molecular context underlying this process remains obscure. Previously, we identified a Tret1 homolog (Nlst8) that is expressed principally in the Malpighian tubules of the brown planthopper (BPH). Here, we used the Xenopus oocyte expression system to show that NlST8 exerts trehalose transport activity that is elevated under low pH conditions. These functional assays indicate that Nlst8 encodes a proton-dependent trehalose transporter (H-TRET1). To examine the involvement of Nlst8 in trehalose reabsorption, we analyzed the sugar composition of honeydew by using BPH with RNAi gene silencing. Trehalose was detected in the honeydew as waste excreted from Nlst8-dsRNA-injected BPH under hyperglycemic conditions. However, trehalose was not expelled from GFP-dsRNA-injected BPH even under hyperglycemic conditions. We conclude that NlST8 could participate in trehalose reabsorption driven by a H+ gradient from the lumen to the principal cells of the Malpighian tubules.